E-government in Europe - Nixon, Paul G.; Koutrakou, Vassiliki N. (Routledge Advances in European Politics, 2007)
This book traces the development of e-government and its applications across Europe, exploring the effects of information and communication technology (ICTs) upon political action and processes. Explores a range of concepts and topics underpinning e-government in Europe: the degree to which e-government translates into genuine reform of government and public administration the dual role of the EU as both a provider of e-government through its own internal activities and also as a facilitator or aggregator in the way it seeks to engender change and promote its ethos in member states across the EU cyberterrorism and its use both by terrorists and governments to pursue political agendas. Featuring in-depth case studies on the progress of e-government in the UK, France, Germany, Denmark, The Netherlands, Portugal, Greece, Slovenia, Hungary, and Estonia. These case studies address the above issues, whilst at the same time highlighting commonality and diversity in practice and the paradox between top-down strategies and the effort to engage wider civil participation via e-government. e-Government in Europe will be of interest to students and scholars of public policy, politics, media and communication studies, computing and information and communications technologies and European studies.